High-dose exposure to synthetic chemicals, hormones, or homeostatic substances in experimental animals or humans can induce artefactual pathology. (10th July 2020) - Smith, Carr J; Perfetti, Thomas A
The maximum tolerated dose (MTD) provides the highest probability of a positive result in a toxicology bioassay. The assumption underlying the MTD in animal bioassays is that adverse effects at very high doses are qualitatively the same as those occurring at low doses. In contrast with the MTD, the optimal top dose in a toxicology animal study is the highest dose that does not produce a pathological end point that presents no risk at lower doses, for example, the dose below which cytotoxicity induces tumors in the absence of genotoxicity or other carcinogenic mechanisms. Normal concentrations or biological activity levels of many substances necessary for normal physiological function induce pathology when found at high levels. For example, the demonstration that ingestion of abnormally high levels of certain dietary fats can cause or exacerbate atherosclerosis in relevant animal models like rhesus macaques does not demonstrate that normal levels of these fats should be considered as toxic. Excessive estrogenic stimulation is associated with breast, ovarian, and endometrial cancers. This does not imply that normal age-appropriate levels of estrogen are toxic. Normal wound healing is associated with transforming growth factors beta 1 and 2. Excessive stimulation of fibroblasts by these growth factors results in hypertrophic scarring and keloid formation. An understanding of the mode of action of a test substance can facilitate the selection of dose levels much higher than those expected to be experienced by humans, but not beyond a dose level at which pathology is an experimental artefact of the high-dose level.